What drives vocational teachers to be innovative? - Febriantina, Susan; Ikhwan, Muhammad; Dara, Despinur; Suwatno, Suwatno; Rulita Nurfaizana, Della (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study explores the impact of leadership, emotional intelligence, information and communication technology (ICT), and knowledge sharing on the innovative work behavior of vocational high school (SMK) teachers in Bekasi Regency, Indonesia. In the context of the Industry 4.0 revolution, vocational education plays a crucial role in preparing youth for the challenges of a rapidly evolving industry. SMK teachers, as frontline educators, are expected to exhibit innovative work behavior to create relevant and impactful learning experiences. However, low levels of innovative work behavior among SMK teachers remain a challenge. Previous studies suggest that factors such as supportive leadership, emotional intelligence, ICT utilization, and knowledge sharing can positively influence innovative work behavior. This research uses a quantitative approach with survey methods to analyze the relationships between these factors and innovative work behavior. The study aims to provide practical insights for educational policymakers and contribute to the theoretical understanding of innovative work behavior in vocational education. Data were collected from 74 teachers in SMKs in Bekasi using structured questionnaires, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings are expected to provide significant contributions to enhancing the innovation of teaching practices in vocational education.